Novel approach for connecting real driving emissions to the European vehicle laboratorial certification test procedure - Varella, Roberto A. (2019)
Vehicle emission certification is evaluated under laboratorial conditions, where vehicles perform a standard driving cycle in controlled conditions leading to several critics, which have resulted in the implementation of the Worldwide harmonized Light Vehicle Test Procedure (WLTP) and the Real Driving Emissions (RDE) testing procedure, as a complementary certification procedure. RDE is still under debate since boundary conditions; evaluation and trip selection methods are still being studied to allow test reproducibility. Currently, the official data analysis method uses the moving average window (MAW_EC), based on the WLTP CO2 emissions for trip validity evaluation (RDE package 4) and emissions (RDE package 3). However, this does not consider the impact of vehicle dynamics. Consequently, this work focuses on developing a novel method to relate certification driving cycle dynamics and on-road test vehicle dynamics, to evaluate RDE tests fuel use and exhaust emissions in a comparable way to certification driving cycles, indicating how close, or far, real-world driving is from the laboratorial certification test. For this, a new method was developed called road vehicle evaluation method (ROVET), which relies on the cycle vehicle dynamic and on-road trip dynamics for assessing if both tests are comparable. Results from 5 measured vehicles with a portable emissions measurement system (PEMS) through reproducibility tests and 2 case studies, show that the ROVET provides results closer to the certification calculated reference than the most commonly used method in Europe (1% avg. difference for ROVET while 8% avg. difference for MAW_EC, regarding CO2 emission, for example). The use of vehicle dynamics on construction and references of a method could be used to incentivize the regulators to review the references used by the current used methods, which suffers several criticisms since their release. As the regulated methods are in constant update, this study could be useful for helping to improve or to be used as additional method for future vehicle certification procedures.